2018
DOI: 10.1007/s11356-018-1270-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in respiratory mortality and short-term effects of air pollutants in Shenyang, China

Abstract: Short-term exposures to air pollution are associated with acute effects on respiratory health. This study aimed to describe 10-year temporal trends in respiratory mortality in the urban areas of Shenyang, China, according to gender and age and estimate the effects of air pollution on respiratory diseases (ICD-10J00-J99) and lung cancer (ICD-10 C33-C34) using a case-crossover design. During the study period 2013–2015, the exposure-response relationship between ambient air pollutants and mortality data was fitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 45 publications
1
20
1
Order By: Relevance
“…Quite a few studies have also reported high effect estimates of O 3 concerning respiratory mortality. A study in Shenyang [34] reported a high and statistically significant effect estimate of 4.7(0.00, 9.9). The non-significance of O 3 may be attributed to several factors including concentration, duration of exposure and susceptibility of the population [35].…”
Section: Discussionmentioning
confidence: 99%
“…Quite a few studies have also reported high effect estimates of O 3 concerning respiratory mortality. A study in Shenyang [34] reported a high and statistically significant effect estimate of 4.7(0.00, 9.9). The non-significance of O 3 may be attributed to several factors including concentration, duration of exposure and susceptibility of the population [35].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suspected that PM deposits differently and perhaps more harmfully in women's lungs compared to men's lungs [32]. However, a meta-analysis indicated that the association of PM 2.5 with lung cancer was stronger for men than for women [33], which was later con rmed by a 10-year time-series study [34]. Analyses of sex differences are more common in occupational epidemiology than in environmental health, because persistent job strati cation by sex has produced marked differences in occupational exposures to chemical agents, ergonomic demands, injury, and psychosocial stressors [9,35].…”
Section: Discussionmentioning
confidence: 99%
“…As the capital of Liaoning Province, Shenyang, located in the center of Northeast Asia and Bohai economic circle, along with the Liaodong Peninsula, is regarded as a comprehensive transportation hub connecting the Yangtze River Delta, Pearl River Delta and Beijing-Tianjin-Hebei to the Kanto region. The research on air pollution in Northeast China has been lacking in recent years, of which the ozone pollution in Shenyang was the most omitting related research covered from 2013 to 2017, methods included the characteristics and differences of basic concentration variations, the effects of meteorological elements and ozone precursors [20,21] and the pollution exposure effects on respiratory diseases and lung cancer mortality [22]. Considering the harsh ozone pollution in Shenyang, along with its special position, we set the study scope in the urban area of Shenyang, scientifically analyze and discuss the pollution situation, which is of great significance to reveal the pollution in typical areas.…”
Section: Study Areamentioning
confidence: 99%
“…The lockdown caused by the epidemic had a positive impact on environmental air and water quality [3]. Decreases in NO 2 levels over China during lockdown (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) February 2020) compared to pre-lockdown (1-20 January 2020) were recognized by satellite data from NASA and the European Space Agency [4]. Concentrations of CO and NO 2 in Almaty, Kazakhstan reduced sharply by 49% and 35%, respectively, during the lockdown compared with the pre-lockdown, except O 3 levels mounted by 15% [5].…”
Section: Introductionmentioning
confidence: 99%